2020
DOI: 10.1021/jacs.0c01629
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidation of β-C(sp3)–H Bonds of Primary Alkylamines through a Rare Four-Membered Palladacycle Intermediate

Abstract: Site-selective functionalizations of C-H bonds are often achieved with a directing group that leads to five-or sixmembered metallacyclic intermediates. Analogous reactions that occur through four-membered metallacycles are rare. We report a challenging palladium-catalyzed oxidation of primary C-H bonds β to nitrogen in an imine of an aliphatic amine, a process that occurs through a four-membered palladacyclc intermediate. The success of the reaction relies on the identification, by a study on H/D exchange, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Having ruled out that CO 2 was serving as a transient directing group, the directing effect must come from the amine. For an insertion mechanism using a mononuclear Pd catalyst, however, that would suggest that a relatively rare four-membered palladacycle would be forming, which we considered unlikely given the lack of either a strongly chelating directing group 64 or bulky substrate. 65 , 66 As previously mentioned, while trying to probe the role of CO 2 , we realized that we could not generate meaningful kinetics data using our cinnamylamine substrates: the initial rates were irreproducible.…”
mentioning
confidence: 99%
“…Having ruled out that CO 2 was serving as a transient directing group, the directing effect must come from the amine. For an insertion mechanism using a mononuclear Pd catalyst, however, that would suggest that a relatively rare four-membered palladacycle would be forming, which we considered unlikely given the lack of either a strongly chelating directing group 64 or bulky substrate. 65 , 66 As previously mentioned, while trying to probe the role of CO 2 , we realized that we could not generate meaningful kinetics data using our cinnamylamine substrates: the initial rates were irreproducible.…”
mentioning
confidence: 99%
“…(1)]. [140] While two key substrate coordinated palladium complexes could be isolated, DFT calculations suggested that the reaction would be likely to involve a rare 4,6-palladacbiycle, unfortunately not isolable.…”
Section: Halogenation and C(sp 3 )à O Bond Formationmentioning
confidence: 99%
“…Hartwig published a mechanistically intriguing method to achieve β-acetoxylation of imines via a strained 4-membered palladacyclic intermediate (Scheme 24). 73 While the reaction required a preformed imine to be effective, hence not transient, it was impressive that such a strained intermediate can be accessed. Salicylaldehyde was found to be an effective directing group along with N-Boc-alanine as a ligand.…”
Section: C(sp 3 )-H Functionalisation Of Aminesmentioning
confidence: 99%